Spatial Trends of Towns in Europe: The Performance of Regions with Low Degree of Urbanisation. (16th March 2017) - Servillo, Loris; Paolo Russo, Antonio
Abstract: The paper contributes to the understanding of socio‐spatial trends and urban systems in Europe, with a specific focus on smaller settlements. First, a morphological delimitation of urban settlements as geographical base is used to identify the different settlement structures that characterise regions across Europe. Secondly, an analysis of population and GDP performances of NUTS 3 regions for the 29 countries of the European space (growth rates in 2001–2011) provides evidence of the variety of territorial phenomena that characterise smaller‐settlement regions across Europe. Finally, the paper highlights the diversity and complexity of urbanisation structures in Europe and how general trends observed at larger scale are articulated locally according to prevailing structures of urbanisation. It shows the character of 'embeddedness' of smaller settlements within urban systems and territorial structures and how the socio‐economic performances of smaller‐settlement regions are defined by a combination of macro trends, national contextualisation, local dynamics and regional path dependency.